POST- LARVAL PRODUCTION OF MACROBRACHIUM ROSENBERG/I USING MASS - CULTURED LIVE FOOD ORGANISMS - Indulkar, S. T.; CHAVAN, J. B.; SHIRGUR, G. A. (Journal of Indian Fisheries Association, 2015)
Macrobrachium rosenbergii post-larvae were produced in 1992 and 1993 using Artemia nauplii and cultured zooplankton Brachionus plicatilis (:rotifier), Apocyclops dengizicus (copepod) and Moina sp. (cladoceran) supplemented with chopped Tubifex worms. In 1992 (first trial) two experiments were carried out under water temperature range of 24.5 to 28.0°C and 26.0 to 28.5°C respectively and corresponding p-ost-larval production was 56.8% and 86.3%. The duration of experiments was 58 and 40 days. During second trial in 1993 water temperature varied between 25.0 to 27 .0°C. At the end of 59 days the post-larvae were found to be 44% of the total number of larvae stocked on the first day.